O best-seller em circulação na escola: um estudo sobre concepções de literatura e experiências de leitura - Oliveira, Iara de (2020)
This work investigates the reception of The bad beginning (1999), by Lemony Snicket's, launched on the market under the name of youthful best-seller. For this, a field research was carried out in two classes of 8th grade of Elementary School II, from two public schools in Goiânia, one federal and one municipal. The research was, therefore, intended to understand how young readers in the school context react to reading a best-seller, as well as the acceptance of this genre in school. In this sense, the reading of The bad beginning was proposed to the young participants, as well as the attitude of teachers, librarians and coordinators of both institutions regarding literature, which, for them, should be read at school. Theodor Adorno (1985), Umberto Eco (1989, 2003, 2011), José Paulo Paes (1990), Sílvia Borelli (1996), Regina Zilberman (1987, 2019), among others, were invited as theoretical, critical and reflective foundations.